Mature IgDlow/- B cells maintain tolerance by promoting regulatory T cell homeostasis - Avijit Ray (Nature Portfolio, 2019)
B cells produce antibodies to mediate various immune functions, but are also reported to negatively regulate immune responses. Here, the authors show that a subset of mature B cells expressing low levels of IgD, present in both mice and human, may pursue this regulatory function indirectly by inducing the proliferation of regulatory T cells via GITRL.